PENGARUH KUALITAS PELAYANAN DAN MOTIVASI MEMBACA TERHADAP KEPUASAN PENGGUNA APLIKASI ISOLO SEBAGAI PERPUSTAKAAN DIGITAL DI DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA SURAKARTA TAHUN 2024 - Isnaini, Isnaini; Suranto, Joko; Wirawan, Riska (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The research conducted aims to analyze the influence of service quality and reading motivation on user satisfaction of the iSolo application at the Surakarta City Library and Archives Service. The service quality variables in this research use the service quality theory by Parassuraman Valerie Zeithmal and Leonard Berry 1988 with the dimensions of tangibles, reliability, responsiveness, assurance and empathy. The reading motivation variable uses self-determination theory by Ryan & Deci in 2000 with the dimensions of autonomy, competence and relatedness. The user satisfaction variable is measured using indicators proposed by Tjiptono, namely conformity to expectations, interest in reuse, and willingness to recommend. The research method used is an associative quantitative method in the form of causal relationships. The population used in this research is all the unknown number of iSolo application users. The sampling technique used simple random sampling or random sampling with a sample of 96 respondents. The method used in collecting research data is a questionnaire. The data analysis technique used is statistical testing with validity, reliability, classical assumption tests, multiple linear regression analysis tests, t tests, F tests, and coefficient of determination tests. Based on the research results, it was concluded that service quality had a low influence on iSolo application user satisfaction at the Surakarta City Library and Archives Service, while reading motivation had a very low influence on iSolo application user satisfaction at the Surakarta City Library and Archives Service. Service quality and reading motivation together have a significant effect on user satisfaction of the iSolo application at the Surakarta City Library and Archives Service with an Fcount value of 26.031. The coefficient of determination value is 0.345, which means that 34.5% of the user satisfaction variable can be explained by the service quality and reading motivation variables, while the remaining 65.5% is influenced by other variables not included in this research. Keywords: Service Quality, Reading Motivation, User Satisfaction